Analisis Pengaruh Praktek Keselamatan dan Kesehatan Kerja terhadap Kinerja Karyawan dimediasi oleh Komitmen Organisasi - Shinta Pradita; Antony Sentoso (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to analyze the effect of occupational safety and health practices on employee performance mediated by work alienation and organizational commitment. This research was conducted on 2 companies engaged in the fabrication industry in the Batu Ampar Industrial Area. The data collection was carried out using the questionnaire method and the number of respondents from this study was 278 respondents. The data analysis method uses the SmartPLS 3.3 application. The results of the validity test of the four variables show the average variance extracted (AVE) value of more than 0.5 and the reliability test results of the four variables show the composite reliability value of more than 0.70 where based on the test results both are valid and reliable and meet the requirements of convergent validity. The results showed that there was a significant effect between occupational safety and health on employee performance mediated by organizational commitment, but there was an insignificant effect between occupational safety and health on employee performance mediated by work alienation